2006
DOI: 10.1186/1743-7075-3-30
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of adipocyte lipogenesis by octanoate: involvement of reactive oxygen species

Abstract: Background: Octanoate is a medium-chain fatty acid (MCFA) that is rich in milk and tropical dietary lipids. It also accounts for 70% of the fatty acids in commercial medium chain triglycerides (MCT). Use of MCT for weight control tracks back to early 1950s and is highlighted by recent clinical trials. The molecular mechanisms of the weight reduction effect remain not completely understood. The findings of significant amounts of MCFA in adipose tissue in MCT-fed animals and humans suggest a direct influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 74 publications
3
19
3
Order By: Relevance
“…Through multiple mechanisms, the n-6 PUFA may reduce SREBP-1c expression or functional protein (Yahagi et al 1999), decreasing the expression of both the FAS and SCD genes. It differs from a previous study suggesting that the MCFA can reduce lipogenic gene expression under in vitro conditions (Guo et al 2006). The SCD transcript concentration in the adipose tissue of CO fed pigs was not different from the animals fed on Control ration.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Through multiple mechanisms, the n-6 PUFA may reduce SREBP-1c expression or functional protein (Yahagi et al 1999), decreasing the expression of both the FAS and SCD genes. It differs from a previous study suggesting that the MCFA can reduce lipogenic gene expression under in vitro conditions (Guo et al 2006). The SCD transcript concentration in the adipose tissue of CO fed pigs was not different from the animals fed on Control ration.…”
Section: Discussioncontrasting
confidence: 99%
“…One of the mechanisms by which n-6 PUFA exert their anti-lipogenic effect is by inhibiting the expression of sterol regulatory element binding protein-1c (SREBP-1c), a transcription factor belonging to basic helix-loop-helix leucine zipper family (Yahagi et al 1999). Limited reports suggest that medium-chain saturated fatty acids (MCFA) may also possess anti-lipogenic effect in the adipose tissue (Guo et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings demonstrated that rosiglitazone dose dependently inhibited ROS production, suggesting that this is how it inhibited MC proliferation. Our results correspond to reports showing that PPAR␥ agonists suppress agent-induced ROS generation (21,27).…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were obtained by Kim et al [15] and Guo et al [16] following studies of the effects of PPAR-c agonists on phorbol ester-treated glioma and osteoblast cells. Thus, while calphostin C is a known inhibitor of PKC, it appears that the PPAR-c agonist rosiglitazone may modulate PKC and/or components of the NADPH-oxidase cascade.…”
Section: Discussionsupporting
confidence: 78%